PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT YANG MENGINTEGRASIKAN KETERAMPILAN TIME TOKEN DAN EFIKASI DIRI TERHADAP HASIL BELAJAR EKONOMI PADA SISWA KELAS X SMA NEGERI 3 KOTA PARIAMAN - Dei Ringga Edwin Dian Negara; Sulastri Sulastri (Program Magister Pendidikan Ekonomi (S2), 2015)
This research is made because the students mark is low. This research is to show the influence of cooperatife learning model of NHT integrate skills time token and self efficacy toward students mark in economy of the students of SMAN 3 Pariaman City. The sampling technique used was purposive sampling, as the result class X6 as the experimental class and class X4 as the control class. Data were collected by using two different instruments. The first one, a questionaire of self efficacy. The other one was on objective test of economy lesson. Data analysis technique is descriptive analysis, inductive analysis and hypothesis testing using two-way Anova. The result of anylising the data showed (1) students’ mark who has studied with cooperatife learning model of STAD of NHT integrate skills time token is higher than the students who are studying in conventional learning process. (2) Students’ mark with high self is higher than the students with low self efficacy. (3) There is no interaction among this learning model, self efficacy to the students mark. Keywords: cooperatife learning model of NHT integrate skills time token, self efficacy, student mark